Bibliometric study of scientific fashion production published in area journals in 2017 and 2018 - Costa, Francisca Carine Farias (Informação em Pauta, 2021)
Introduction: fashion conveys our visual identity and is able to determine time, age, work environment, country of origin and musical taste, so it is a very important area. Objective: to know the scientific production in the fashion area. Methodology: quali-quantitative research, which used bibliographic research for theoretical foundation and as a method for data collection, the analysis of citations, enabling the characterization of the area. Results: Gilles Lipovetsky as the most cited author; predominance of individual authorship (70%); high level of title of the authors, where 48% have a doctorate; great concentration of authors in the southern region of the country (45%), being more expressive in São Paulo. The most frequent theme in the articles was design; the average age of citations is less than 14 years; obsolescence is approximately 11 years; the type of document most cited was a national book and/or chapter; the most cited scientific journal was ModaPalavra e-periodical; and, the most used language is Portuguese (65%). Conclusions: bibliometrics, through citation studies, is an important indicator of scientific activity, helps the development of collections and service management for libraries that have the course, and, helps in the organization and systematization of scientific and technological information.